2017
DOI: 10.1126/sciadv.1700935
|View full text |Cite
|
Sign up to set email alerts
|

Extensive arsenic contamination in high-pH unconfined aquifers in the Indus Valley

Abstract: Fifty million to 60 million people potentially exposed to high levels of groundwater arsenic, which is coincident with areas of irrigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
113
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(126 citation statements)
references
References 61 publications
2
113
1
Order By: Relevance
“…Alarmingly high levels of As in Pakistan's ground water also in surface water have been found [15]. It is recently reported that more than 50 million people in Pakistan were at a risk of arsenic poisoning because most of Pakistani communities use groundwater for drinking and other households polluted with arsenic [16]. Previous studies of 1990's had revealed that groundwater in some areas of Pakistan also contained high levels of arsenic while the extent of those risks was still unknown [17].…”
Section: Aqueous Arsenic Contamination In Pakistanmentioning
confidence: 99%
See 4 more Smart Citations
“…Alarmingly high levels of As in Pakistan's ground water also in surface water have been found [15]. It is recently reported that more than 50 million people in Pakistan were at a risk of arsenic poisoning because most of Pakistani communities use groundwater for drinking and other households polluted with arsenic [16]. Previous studies of 1990's had revealed that groundwater in some areas of Pakistan also contained high levels of arsenic while the extent of those risks was still unknown [17].…”
Section: Aqueous Arsenic Contamination In Pakistanmentioning
confidence: 99%
“…In 2003, another PCRWR team worked on it, ground water samples were collected at 1,184 sites throughout the country, taken from wells down into the Earth till 100 feet. The team then used statistical methods to construct a hazard map and to estimate the size of population exposed to the threat [16,20]. According to a study conducted by Podgorski et al [16] and based on samples from 1,184 wells across the country actually proved that the process of boiling or filtration were not helpful to remove arsenic from groundwater.…”
Section: Aqueous Arsenic Contamination In Pakistanmentioning
confidence: 99%
See 3 more Smart Citations